(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The current article is a tutorial aiming to guide PhD students and research in the creation of maps using Geographic Information System methods. In particular, this tutorial focuses on the collection of data from the database OpenStreetMaps via the software QGIS. Using a case study about Small and Medium Enterprises involved in the acquisition, repair, and reselling of second-hand goods in the city of Tashkent, the present article will explain how to analyse a combination of geographic and social data on a map. The present research seeks to show the multifaceted aspects of responsible consumption in an urban setting.